The impact of loneliness and anonymity on self-disclosure among social media X users - Maindah NurLaili Asari; Tatik Mukhoyyaroh (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
The rapid development of social media enables individuals to self-disclose on communication sites within social media. This study examines the influence of loneliness and anonymity on self-disclosure among users X (Twitter). The subjects of this research are X users with anonymous accounts ranging from 17 to 40 years old, totaling 356 participants. Employing a quantitative approach, the researcher adopted the Revised Self-Disclosure Scale (RSDS) to measure the self-disclosure variable, the UCLA Loneliness version 3 to measure loneliness, and the Lee, Choi, and Kim anonymity scale to measure anonymity. The research results indicate that both loneliness and anonymity, both partially and simultaneously, impact the self-disclosure of social media X users.